Urban accessibility: the paradox, the paradigms and the measures. A scientific review - Guida, Carmen; Caglioni, Matteo (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The literature review presented in this paper represents a part of a wider research focused on the elderly quality of life within urban environments and aimed at designing innovative tools for both public administrations and elderly citizens. The article presents a systematic review of the relevant literature regarding the development of the accessibility concept during the 1959-2020 period. Nearly 6,000 documents were selected from the Scopus database, using the keywords “urban accessibility” and limiting the results to the fields of Urban Studies and Social Sciences to select the documents for the bibliometric analyses run. They were run in R Studio environment through a tool, developed in 2017, named bibliometrix. These analyses were run to highlight the main traits of the urban accessibility concept and developed methodologies and measures, in order to implement it in real-world practices and tools. The extensive and systematic literature review shows that for many years much of this scientific production has a deep theoretical nature, rather than practical. That was mostly due to difficulties in computing and introducing accessibility measures in decision-making practices. The advent of GIS has made much more practical the development of accessibility-oriented planning tools, and many commercial packages are now available.